TNF-α exacerbates postoperative plantar pain by regulating the expression of Nav1.8 - Zilu Shang; Yu Li; Yun Zhang; Yajuan Gong (PLoS ONE, 2026)
Postoperative pain (POP) is one of the most common complications of surgical procedures. Using a rat plantar incision model, we investigated the interactions between tumor necrosis factor-α (TNF-α), nuclear factor-κB (NF-κB), and the voltage-gated sodium channel Nav1.8, to uncover the neural basis of POP. Our research demonstrates that, within the dorsal root ganglion (DRG), TNF-α enhances pain behaviors by driving NF-κB–dependent overexpression of Nav1.8 in neurons, further elucidating the molecular basis of POP. This study identifies the TNF-α/NF-κB/Nav1.8 axis as a critical pathway for therapeutic intervention, thereby establishing a theoretical foundation for targeting cytokine signaling to alleviate POP.